How to Check the Answers in Quadratic Equations

104 4
    • 1). Write the quadratic equation and the roots that you calculated. For example, let the equation be x² + 3x + 2 = 0, and the roots be -1 and -2.

    • 2). Substitute the first root into equation and solve. For this example, substituting -1 into x² + 3x + 2 = 0 results in (-1)² + 3(-1) + 2 = 0, which becomes 1 - 3 + 2 = 0, which is 0 = 0. The first root, or answer, is correct, since you get 0 when you replace the variable "x" with -1.

    • 3). Substitute the second root into the equation and solve. Substituting -2 into x² + 3x + 2 = 0 results in (-2)² + 3(-2) + 2 = 0, which becomes 4 - 6 + 2 = 0, which is 0 = 0. The second root, or answer, is also correct, since you get 0 when you replace the variable "x" with -2.

Source...
Subscribe to our newsletter
Sign up here to get the latest news, updates and special offers delivered directly to your inbox.
You can unsubscribe at any time

Leave A Reply

Your email address will not be published.